Digital versus Traditional: Secondary Students with Visual Impairments' Perceptions of a Digital Algebra Textbook. (January 2016) - Bouck, Emily C.; Weng, Pei-Lin; Satsangi, Rajiv
Introduction: Digital textbooks are increasingly marketed and used, yet little research examines this medium. Within the limited research, even less investigates the role of digital textbooks in mathematics—a challenging content area for many students, but especially for students with visual impairments. Methods: Through a qualitative analysis, this study sought to understand the nature of the use of a digital algebra textbook to support secondary students with visual impairments in algebra. Results: The results suggest three main themes: (a) students' dependence on their traditional textbook medium, (b) educators' reactions to the technology, and (c) the benefits of using the digital textbook despite resistance. The three themes culminate in clear student preferences for traditional textbooks. Discussion: The general resistance to use of the technology warrants caution in terms of schools moving forward with the adoption of digital textbooks, and it suggests that additional examination of the topic is needed. Implications for practitioners: Practitioners can consider using digital textbooks, but they will need to ensure that they and their students are both properly motivated and adequately trained to use such technology.